Optimized Search Model using Sensing and DCG Approach - Geetha, V; Akilandeswari, V (International Journal of Computer Sciences and Engineering, 2025)
Web search engine has long been the most important portal for ordinary people looking for useful information on the web. However, users may fail when search engines offer inappropriate results that do not meet their real intentions. Personalized Web Search (PWS) is a general category of searching for personalized search results, which is suitable for personal user needs. To protect user privacy in PWS based on profile, researchers need to consider two important and conflicting issues during search process. The first problem is that they try to improve the search quality with the application to customize the user profile. The existing methodology, to protect user privacy in PWS based on profile, researchers need to consider two important and conflicting issues during search process. The first problem is that they try to improve the search quality with the application to customize the user profile. In the proposed work, the information retrieval process may be split into two tasks, the retrieval of items and the ranking of the retrieved items. The retrieval is often performed using an inverted index, which contains of all the indexed terms. There are numerous advantages that can be taken from personalization content particularly to advertisers that need to build deals profit out of suggestions